EDUCATION OF DIABETIC FOOT CARE IN PATIENTS WITH DM IN THE WORKING AREA OF PUSKESMAS 1 ULU - Sulistini, Rumentalia; Mediarti, Devi; Syokumawena, Syokumawena (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The community service activities that have been performed were aimed at increasing the community knowledge, especially cadres and patients with diabetes mellitus, in diabetic foot care. Increasing trends of diabetes cases will also increase the incidence of foot ulcers. Therefore, it is important for cadres and community members to understand diabetic foot care. This community service activity consists of several stages; preliminary survey, implementation of activities, and evaluation. This activity involved health workers at the Puskesmas, five cadres, and 21 people with diabetes. Participants were very enthusiastic in answering and asking questions in educational activities. The patient also gets foot and wound care during this activity. This activity needs to be conducted continuously to prevent further complications from diabetes.